2004
DOI: 10.1177/0886260503262083
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Online Harassment at a University Campus

Abstract: This exploratory study of 339 students at the University of New Hampshire found that approximately 10% to 15% of students reported receiving repeated e-mail or Instant Messenger (I-M) messages that "threatened, insulted, or harassed," and more than half of the students received unwanted pornography. Approximately 7% of students reported online harassment to an authority. Messages originated from strangers, acquaintances, and significant others. No difference in online harassment was found based on demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
275
3
36

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(331 citation statements)
references
References 9 publications
17
275
3
36
Order By: Relevance
“…Furthermore, homophobic bullying is not exclusively targeted at those who identify as LGBT but also those perceived to be. A few studies have considered the prevalence of cyberbullying, the use of technology to mediate bullying behaviour, amongst LGBT aged 11 to 22 (Blumenfeld and Cooper 2010), and undergraduate students (Finn 2004). It was reported that almost half of respondents would not report an act of cyberbullying against them to a parent or guardian (Blumenfeld and Cooper 2010).…”
Section: Bullying Amongst Lgbt Youthmentioning
confidence: 99%
“…Furthermore, homophobic bullying is not exclusively targeted at those who identify as LGBT but also those perceived to be. A few studies have considered the prevalence of cyberbullying, the use of technology to mediate bullying behaviour, amongst LGBT aged 11 to 22 (Blumenfeld and Cooper 2010), and undergraduate students (Finn 2004). It was reported that almost half of respondents would not report an act of cyberbullying against them to a parent or guardian (Blumenfeld and Cooper 2010).…”
Section: Bullying Amongst Lgbt Youthmentioning
confidence: 99%
“…However, these phenomena are not only present in adolescence, they also occur during the university years with young adults (Akbulut & Eristi, 2011;Azevedo, 2013;Dilmaç, 2009;Finn, 2004;Francisco, 2012;Kraft & Wang, 2010;Souza, 2011;Walker, Sockman, & Koehn, 2011). Finn (2004) mentioned that what may lead to cyberbullying, is the easy access the university population has to the Internet and the wireless network in universities and faculties (in student residencies, libraries, etc.). In Finn's study, 10-15% of 339 students from New Hampshire University had received e-mails or instant messages related to online harassment from strangers, acquaintances, or a significant other.…”
Section: Cyberbullying In Higher Educationmentioning
confidence: 99%
“…Also because of the potential reasons for the high frequency of school violence that are possibly related to the sudden and drastic biological and social changes experienced by adolescents (Li, 2007). However, these phenomena are not only present in adolescence, they also occur during the university years with young adults (Akbulut & Eristi, 2011;Azevedo, 2013;Dilmaç, 2009;Finn, 2004;Francisco, 2012;Kraft & Wang, 2010;Souza, 2011;Walker, Sockman, & Koehn, 2011). Finn (2004) mentioned that what may lead to cyberbullying, is the easy access the university population has to the Internet and the wireless network in universities and faculties (in student residencies, libraries, etc.).…”
Section: Cyberbullying In Higher Educationmentioning
confidence: 99%
“…Además, un 47,6 % declaró haber acosado a su pareja a través del teléfono móvil y un 14 % a través de internet, siendo mayor el porcentaje de chicos acosadores. En otro estudio con población similar (Finn, 2004), se encontró que entre el 10 % y el 15 % habían sido víctimas de acoso por parte de sus parejas. Zweig y cols.…”
unclassified